Governança da água no Ceará: uma visão sistêmica - Moreira, Maria Lúcia de Sousa (2017)
In Ceará, the management of water resources and governance of its waters is a relevant topic for the State, which has almost its entire area within the semi-arid region of Brazil. Historically, measures have been taken with the aim of resolving the harmful effects of water scarcity. Strategies aimed at building dams were important at the beginning of the 20th century, with Ceará being a pioneer in dam policy. The construction of these reservoirs, however, could not do without a broader policy that involved the management of water resources. At the beginning of the 1990s, Ceará anticipated drafting legislation aimed at water management. In this way, a regulatory management of water use is instituted to demand, from the institutionality, na ordering of actions between the State, entities and various actors involved. In this sense, the research assumes that there is water governance in the State of Ceará and that conceptually governance includes the management of water resources. As a general objective, we intend to analyze whether water governance in the State is systemic from the perspective of the General Systems Theory (TGS). In this way, the analysis pursues the principles, purposes and categories of TGS according to Ludwig von Bertalanffy. In this context, water governance and consequently the management of water resources in Ceará are studied, observing the diferente realities and the hegemonic role of the State as regulator. As support for the analysis, documentary research and bibliographic research are used as methodological resources. The first will consist of the collection of main documents at state level focusing on the State Water Resources Policy of Ceará. The second will bring artifacts made up of theses, dissertations, books and articles that discuss this issue. The research identifies elements that can define water governance in the State, but that are not explicitly declared as governance and that can generate misinterpretations and even possible failures in its implementation and application of the Law.